PENDAMPINGAN TERHADAP KEMAMPUAN BELAJAR CALISTUNG SISWA KELAS IV SEBELUM DAN SESUDAH PEMBELAJARAN DI SDN 75 BENTANG - Irma Novita; Reski Ardilla S; Nasrah (STKIP Subang, 2025)
This study aims to determine the differences in the reading, writing, and arithmetic (calistung) abilities of fourth-grade students before and after the learning process. The research subjects were 15 fourth-grade students of SDN 75 Bentang, Galesong District, Takalar Regency. Data collection was conducted through direct observation, field notes, and short interviews with students after the learning activities. The results of the study showed an increase in student abilities after participating in intensive calistung learning for one week. In the reading aspect, students who were able to read fluently increased from 40% to 86.6%. In the writing aspect, students who wrote with correct and neat spelling increased from 46.6% to 80%. Meanwhile, in the arithmetic aspect, students who were able to complete two-digit addition and subtraction operations increased from 33.3% to 93.3%. Thus, calistung learning has a positive impact on improving students' academic abilities and self-confidence.